Ответы и объяснения

2013-03-10T00:18:47+04:00

(х^2+х-2)(х^2+х+3)-36=0

пусть  х^2+х=t

(t-2)(t+3)-36=0

t^2+t-42=0

t1=-7     t2=6

x^2+x+7=0                                                                x^2+x-6=0   

D1-28<0 действительных корней нет             х1=-3     х2=2

Сумма = -3+2=-1

Ответ:-1

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

2013-03-10T00:20:02+04:00

(х^2+х-2)(х^2+х+3)-36=0

(x-2)*(x+3)*(x^2+x+7)=0

 

x-2=0                x+3=0               x^2+x+7=0

x=2                    x= -3                    D=1^2-4*1*7= -27

Ответ: 2; -3